Feasibility, usability, and acceptance of “Brain-IT”—A newly developed exergame-based training concept for the secondary prevention of mild neurocognitive disorder: a pilot randomized controlled trial - Manser, Patrick; Poikonen, Hanna; de Bruin, Eling D. (Frontiers in Aging Neuroscience, 2023)
Background Exergames provide a promising new approach to implement simultaneous motor–cognitive training, which may support preventing the decline in cognitive functioning in older adults who have a mild neurocognitive disorder (mNCD). Objectives To evaluate feasibility, system usability, and acceptance of “Brain-IT”, a newly developed training concept combining exergame-based motor-cognitive training and heart rate variability (HRV) guided resonance breathing for the secondary prevention of mNCD. Methods A pilot randomized controlled trial (RCT) with an allocation ratio of 2:1 (i.e., intervention:control) was conducted. The control group proceeded with usual care. The intervention group performed a 12-week training according to the “Brain-IT” training concept implemented with the “Senso Flex” (Dividat AG) exergaming system in addition to usual care. Feasibility and usability outcomes were analyzed using descriptive statistics. User acceptance was analyzed qualitatively and using Friedman analysis of variance (ANOVA), as well as Wilcoxon signed-rank tests. Results Eighteen participants (77.3 ± 9.8 years; 44.4% females) were included. On average, we recruited 2.2 participants per month, and 35.3% of the individuals contacted were included. The intervention group had an attrition rate of 20% and mean adherence and compliance rates of 85.0 and 84.1%, respectively. The mean system usability score, measured with the system usability scale, was 71.7. High levels of exergame enjoyment, an increase in exergame enjoyment, and internalization of training motivation with large effect sizes (p = 0.03, r = 0.75 and p = 0.03, r = 0.74, respectively), as well as acceptable perceived usefulness, were observed. Preliminary data on the effects of the “Brain-IT” training are promising. Conclusion The feasibility and usability of the “Brain-IT” training are acceptable. However, frequent occurrences of technical problems and difficulties in using the exergame training system were identified as barriers to performing the “Brain-IT” training. To optimize feasibility, either improvements or alternative solutions are required in the hardware and software of the exergame used to implement the “Brain-IT” training. The “Brain-IT” training itself was well-accepted by older adults who have mNCD. Therefore, the effectiveness of the “Brain-IT” training concept should be investigated in future studies. Trial registration clinicaltrials.gov/ct2/show/NCT04996654.